Pengaruh Variasi Proses Annealling Pada Performa Core Losses Trafo 1 Fasa E-I - Nurhadi, Slamet; Anang Dasa Nofvowan; Satria Luthfi Hermawan; Binar Surya Gumilang (Elposys: Jurnal Sistem Kelistrikan, 2025)
Transformers have key role in converting voltage level to suit several applications, ranging from industries to residential areas. As part of the local content product production initiated by the government, it is essential to identify the material quality to yield good performance. Therefore, developing a well-designed core material is substantial to prevent excessive transformers core losses during operation. The core losses performance due to the annealing process of the silicon steel core is presented in this research. The E-I core shape is chosen to imitate the existing distribution transformers. The design aims for the optimal core losses of the EI transformers. The design process involves the selection of the iron core and calculating the number of coil turns on the primary and secondary sides. Based on experimental results, under the same number of winding turns, no significant change in transformers impedance due to the annealing process duration. Testing with a nichrome wire load shows that Transformers 1, with a flux density of 1, achieves efficiency and voltage regulation close to 100%. The second test with the addition of a rectifier indicates a decrease in efficiency and regulation, with Transformers 3 and a flux density of 1,6 providing the best results. The research findings show that a smaller flux density in transformer results in better efficiency and regulation for AC output, while a larger flux density supports better efficiency and voltage regulation for DC output. These findings can serve as a guide in designing EI Transformers for optimal battery charging systems.